Role-play as a didactic strategy enhancing the speaking skills in High-School students - Cruz Murillo, Alisson (2023)
Role-play has emerged as a valuable didactic strategy for enhancing the speaking skill in students, as it immerses them in language-rich contexts, prompting active communication. Therefore, the purpose of this study is to analyze the use of role-play as a didactic strategy for enhancing the speaking skills of EFL high school students of Bahia de Caraquez city. A qualitative research design was employed drawing upon the insights of three expert English teachers of first year of high school, from 3 public schools of the Bahía de Caraquez city. As well, 40 relevant scientific articles were reviewed, sourced from reputable databases, including Google Scholar, Redalyc, and Scielo. Main results showed that role-plays allow students to explore authentic situations, focus on communication rather than grammar, and reduce stress and anxiety. Teachers can create a supportive and safe environment for students to practice speaking, assess and evaluate their speaking skills, incorporate technology, and promote language diversity and cultural sensitivity.   It is concluded that public English teachers of Bahia de Caraquez city use role-play as a didactic strategy for enhancing the speaking skills of EFL high school students.